2018
DOI: 10.1080/13625187.2017.1422239
|View full text |Cite
|
Sign up to set email alerts
|

Ongoing or previous mental disorders predispose to adverse mood reporting during combined oral contraceptive use

Abstract: Women with ongoing or previous mental disorders or risk use of alcohol have greater risk of COC-induced mood symptoms. This may be worth noting during family planning and contraceptive counselling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
33
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 33 publications
0
33
1
1
Order By: Relevance
“…Previous research has reported that most depressions begin during adolescence [27] and that 10-20% of adolescents have had at least one major depressive episode by the age of 18 years [35]. Further, a recently published study concluded that women with ongoing or previous mental disorder had a greater risk of COC-induced mood symptoms [36].…”
Section: Depression and Hormonal Contraceptionmentioning
confidence: 99%
“…Previous research has reported that most depressions begin during adolescence [27] and that 10-20% of adolescents have had at least one major depressive episode by the age of 18 years [35]. Further, a recently published study concluded that women with ongoing or previous mental disorder had a greater risk of COC-induced mood symptoms [36].…”
Section: Depression and Hormonal Contraceptionmentioning
confidence: 99%
“…7 8 Other studies have reported that women with previous or ongoing psychological symptoms, mental disorders or impulsive or antisocial behaviours typically exhibit an inconsistent use of contraception. [9][10][11] According to other studies, the risk of unintended pregnancy is also elevated in women with eating disorders. 12 However, systematic data on their HC use are still lacking, and the subject needs to be further studied.…”
mentioning
confidence: 93%
“…The review also reported that women with underlying mood disorders might have a predisposition to mood effects with CHC [12]. This conclusion was supported by the findings of a recent study by Bengtsdotter et al [20] The authors went further to suggest that women with no psychiatric history have little risk of developing mood symptoms with use of CHC [20].…”
Section: Risk Of Mood Symptoms and Hormonal Contraceptionmentioning
confidence: 74%